THE EFFECT OF PRODUCT QUALITY TOWARDS INTEREST IN BUYING â€œROTI KEMBUNGâ€ - hamdani, Nizar Alam; Fauziah, wulan (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2020)
The influence of Globalization and Modernization in the industry today has led to the rise of increasingly fierce and competitive business competition in the domestic and national markets. Quality products in culinary SMEs within the company are essential because, with no quality products, they will not be able to compete. This study tries to measure the level of interest in buying food "Roti Kembung" influenced by product quality. This research uses quantitative. The data collection method uses the survey method. The target population is puffed bread consumers who have consumed "Roti Kembung" products, with the sample for this study being 32 respondents. Respondent characteristics that determine this researcher are people who have already consumed "Roti Kembung". Based on the research results on the quality of bread products, positive convex toward repurchase interest has a significant total effect. Improving the quality of this product will enhance product quality. Therefore, it is necessary to strengthenÂ  Â product quality supported by selecting the right ingredients and making product differentiation.